Pacific Possible : Long-term Economic Opportunities and Challenges for Pacific Island Countries - World Bank (Washington, DC, 2017)
Pacific Possible is a program of research and dialogue focusing on long term economic growth perspectives of Pacific Island Countries. It analyzes the major transformational economic opportunities and challenges which include tourism, labor mobility, ICT, oceanic tuna fisheries, deep sea minerals, climate change and natural disasters, and non-communicable diseases. This report summarizes and synthesizes research undertaken on these topics. Detailed background papers on these topics are also available as part of the Pacific Possible series.